When Polanyi met Farage: Market fundamentalism, economic nationalism, and Britain's exit from the European Union - Hopkin, Jonathan (British Journal of Politics & International Relations, 2017)
The vote for Brexit is not an isolated event, but part of a wave of populist, anti-elite revolts: a new 'anti-system' politics Western democracies are experiencing, shaking the existing consensus around economic integration, free markets and liberal values. This wave takes a variety of forms, but has in common a robust, even violent, rejection of the mainstream political elites and their values, and a demand for governments to act on the sources of social and economic distress and inequality. This article views Brexit as a part of this new anti-system politics, a reaction to the decline in ideological competition in democracies and the increasing impotence of politicians to address the upheavals wrought by global free market capitalism. This reaction has become particularly acute after the financial crisis of the late 2000s, which affected Britain disproportionately, and the failure of austerity policies to revive growth, crystallising the ineffectiveness of existing policies to deal with economic stagnation and cultural change. This policy failure is compounded by a perceived refusal of politicians to engage with the broader public and a lack of real choice between the mainstream political parties. The article will present evidence that a failed policy consensus, a rise in inequality and a decline in the representativeness of political elites, rather than a resurgence of intolerance or xenophobia, are the principal causes of the Brexit vote.
Keywords: Brexit; British economic policy - 2010-; British withdrawal from the European Union, 2016-; Europe - Foreign relations - Great Britain; European Union; Great Britain - politics & government - 2007-; economic nationalism; economics; markets; membership; nationalism; protectionism

What can Okun teach Polanyi? Efficiency, regulation and equality in the OECD - Hopkin, Jonathan; Blyth, Mark (Review of International Political Economy, 2012)
Arthur Okun famously argued that “effciency is bought at the cost of inequalities in income and wealth”. Okun's trade-off represents the antithesis to Karl Polanyi's view of the relationship that the more embedded markets are in society, the better the social and economic outcomes they produce. This paper refines both these views. We argue that not all forms of market embeddedness are created equal, and that the relationship between equality and efficiency can be both positive and negative. We show this by examining how different ways of embedding economic activity in society through market regulation produce different combinations of efficiency and equality. We identify empirically three broad patterns: market liberal regulatory frameworks that promote competitive markets without decommodifying institutions; embedded liberal regulations that allow markets to work efficiently, but within the framework of decommodification and equality; and embedded illiberalism, where regulations hinder markets in favor of powerful social groups and where decommodification undermines both efficiency and equality. Okun's trade-off emerges as a special case limited to the English-speaking democracies: other OECD countries tend to exhibit either efficiency and equality together, or inefficiency and inequality together. These findings suggest a corrective to both nave market liberal views of the incompatibility of efficiency and equality, but also to the more sophisticated Varieties of Capitalism framework, which pays insufficient attention to the ways in which markets can be embedded in stable but apparently dysfunctional institutional arrangements.
Keywords: OECD; OKUN, Arthur; critique; embeddedness; international political economy; regulation